Wake up : a life of the Buddha - Kerouac, Jack, 1922-1969 (Penguin Books, 2009)
Though raised Catholic, in the early 1950s Jack Kerouac became fascinated with Buddhism, an interest that would have a profound impact on his ideas of spirituality and their expression in his writing. Published for the first time in book form, this is Kerouac's retelling of the story of Prince Siddhartha Gautama, who as a young man abandoned his wealthy family and comfortable home for a lifelong search for enlightenment. As a compendium of the teachings of the Buddha, Wake Up is a meditation on the nature of life, desire, wisdom, and suffering. Distilled from a variety of canonical scriptures, Wake Up serves as both a concise primer on the concepts of Buddhism and as a document of Kerouac's evolving beliefs. It is the work of a devoted spiritual follower of the Buddha who also happened to be one of the twentieth century's most influential novelists.--From publisher description.